ChemInform Abstract: Diastereo‐ and Enantioselective Iridium Catalyzed Carbonyl (α‐Cyclopropyl)allylation via Transfer Hydrogenation. Issue 4 (January 2016) - Tsutsumi, Ryosuke; Hong, Suckchang; Krische, Michael J.
Abstract: Using the chiral precatalyst modified by SEGPHOS, the carbonyl α‐(cyclopropyl)allylation is reached with similar facility from alcohol or aldehyde oxidation levels of the substrates.